Exploring the Attitude of Greek Kindergarten and Primary School Teachers towards Inclusive Education (Journal of Advanced Research in Social Sciences, 2018)
The present study was carried out during the school year 2014-2015 in the Region of Epirus with the participation of kindergarten teachers (N:217) and primary school teachers (N:303) and examines the attitude of Greek teachers towards the inclusion of children with special educational needs and/or disability in the general education classes. High-quality teaching in these classrooms is an essential factor for the successful participation of students in preschool and school education as well as for their transition to the next levels of school. The proper education of teaching staff and unified education constitute the objectives of the modern school system.